Incorporating specific sambo exercises into distance learning for high school students aged 15-16 - Valeriia Zakharevich; Georgiy Korobeynikov; Olena Nesen; Abdulaziz Xamidjonov (Physical Culture, Recreation and Rehabilitation)
Background and Study Aim. The military situation in Ukraine necessitates a revision of the school class organization system. Proximity to the military contact line forces schools to switch to online learning. Additionally, there is a decrease in physical activity among school students. In these conditions, it is important to explore the effectiveness of using specific sambo exercises to develop physical qualities in high school students during distance learning. The aim of the study is to determine the effectiveness of such application of sambo exercises for the development of physical qualities in high school students in a distance learning format.